Photodynamic therapy in surgical treatment of patients by a skin melanom - G. I. Gafton; Yu. V. Semiletova; V. V. Anisimov; M. L. Gelfond; M. Yu. Myasnyankin; A. V. Novick; T. L. Nekhayeva; I. A. Balduyeva; I. G. Gafton (Сибирский онкологический журнал)
In experimental and clinical research carried out studying of influence of neoadjyuvant photodynamic therapy on T- and B-cellular immune answer in surgical treatment of patients of a melanoma of skin of the I–III stage. PDT was executed to 25 patients two days prior to surgical removal of primary tumor from July, 2012 to January, 2013. As a result of the conducted research it was revealed that: the increase in concentration fotoditaziny doesn‘t lead to increase in quantity of tumoral cages at stages early apoptosis; lengthening of time of an exposition leads to increase in a share of late forms apoptosis, and FDT use with fotoditaziny in a dose of 50,0 mg with the subsequent radiation (662 nanometers, 400 J) in 2 days prior to surgical intervention promotes T- and B-cellular link of immune system.